Analysis of Gas Well Classifications and Productivity Influencing Factors in Kela-2 Gas Field - LIU, Zhaolong; ZHANG, Yongzhong; LIU, Hualin; LV, Zhikai; HUANG, Weigang (CT&F - Ciencia, Tecnología y Futuro, 2021)
As one of the main gas fields in Chinese West-East Gas Transmission Project, cumulative gas production of Kela 2 Gas Field has been over 120 billion cubic meters since 2004. Each gas well has different gas production characteristics, water production, and pressure changes. Advanced water results in a serious non-homogeneous water invasion, and the actual gas production is much less than that in the development scheme. To further enhance the recovery of the Kela 2 Gas Field, productivity influencing factors of each gas pay interval are analyzed by using the production logging data based on geological characteristics. According to the change of the main gas pay and water production from production logging, gas wells are divided into four types, and three water invasion patterns in Kela 2 Gas Field. The causes of gas production changes and water production regime are analyzed for each type first, and then the main productivity influencing factors in gas wells are determined. The outcome shows that pressure drop, water breakthrough of gas pay layers, and different reservoir properties are the main productivity influencing factors. Through gas well classification of the Kela 2 Gas Field, the productivity influencing factors and productivity change regime are determined, which could provide grounds for further enhancing the recovery of the Kela 2 Gas Field.